2022
DOI: 10.1039/d2sc00202g
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic C(sp3) radical generationviaC–H, C–C, and C–X bond cleavage

Abstract: C(sp3) radicals (R·) are of broad research interest and synthetic utility. This review collects some of the most recent advancements in photocatalytic R· generation and highlights representative examples in this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 220 publications
0
44
0
Order By: Relevance
“…An increasing body of research from recent years has shown that the intake, digestion, and absorption of dietary meat protein can significantly affect physiological functions and metabolic changes. [ 11–13,27 ] The results of this study indicate that compared with the XWH0 and XWH1 groups, the body weight gain and epididymal fat weight decreased after XWH2 and XWH3 intake, suggesting that the prolonging of ripening period of Xuanwei ham may affect its nutrient digestibility and fat accumulation. Casein intake has been reported to help prevent weight gain among the protein sources tested, [ 28,29 ] and was consistent with the body weight change in Casein group observed in this study.…”
Section: Discussionmentioning
confidence: 83%
“…An increasing body of research from recent years has shown that the intake, digestion, and absorption of dietary meat protein can significantly affect physiological functions and metabolic changes. [ 11–13,27 ] The results of this study indicate that compared with the XWH0 and XWH1 groups, the body weight gain and epididymal fat weight decreased after XWH2 and XWH3 intake, suggesting that the prolonging of ripening period of Xuanwei ham may affect its nutrient digestibility and fat accumulation. Casein intake has been reported to help prevent weight gain among the protein sources tested, [ 28,29 ] and was consistent with the body weight change in Casein group observed in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Pioneered by MacMillan, Molander and others ( Chan et al., 2022 ; Huang et al., 2022 ; Tellis et al., 2016 ; Twilton et al., 2017 ), metallaphotoredox cross-couplings have gained exponential growth in both academic and industrial platforms for the last decade. These novel synthetic paradigms could synergize the advantages of rapidly developed molecular photochemistry and well-established transition metal catalysis, thus opening uncharted chemical space for new mechanistic insights and long-sought-after reactivities.…”
Section: Before You Beginmentioning
confidence: 99%
“…Escitalopram is primarily metabolized in the liver by cytochrome P (CYP)450, particularly CYP2C19, which is a highly polymorphic enzyme that causes interindividual pharmacokinetic differences (Rao, 2007;Pastoor and Gobburu, 2014), and is excreted mainly through the kidneys. The effect of age (Dolder et al, 2010;Yang and Scott, 2010), gender (Montejo et al, 2015), smoking (Oliveira et al, 2017;Scherf-Clavel et al, 2019), CYP2C19 phenotype (Huang et al, 2021), hepatic impairment (Areberg et al, 2006), and renal impairment (Dolder et al, 2010) on the pharmacokinetics of escitalopram have been investigated. The findings of these studies were instrumental in developing specific dosing recommendations for escitalopram for specific populations (Hicks et al, 2015;Brouwer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%